Impact of Sales Promotion, Store Atmosphere, Hedonic Motivation, and Fashion Involvement on Impulsive Buying Behavior in Shopee Live Streaming with Positive Emotion as a Mediator - Purwanto, Agnes Debora Bernice; Irwansah, Indra Rizki; Sanny, Lim (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2025)
The rapid growth of online shopping in Indonesia has led platforms like Shopee to implement live streaming to enhance customer engagement and encourage impulsive purchases. This study examines the effects of sales promotion, store atmosphere, hedonic motivation, and fashion involvement on impulsive buying behavior in Shopee Live streaming, with positive emotion serving as an intervening variable. Utilizing a quantitative approach, data was collected from 200 Shopee users in Jakarta through purposive sampling. Structural Equation Modeling (SEM) was applied for data analysis to test the relationships between variables. Results indicate that sales promotion, store atmosphere, hedonic motivation, and fashion involvement significantly influence impulsive buying behavior directly and through positive emotion. The findings reveal that positive emotion plays a crucial mediating role, particularly with sales promotions, hedonic motivation, and fashion involvement, enhancing impulsive buying tendencies. These insights offer valuable implications for e-commerce platforms and marketers aiming to optimize live-streaming features to drive impulsive purchases through engaging and emotionally resonant experiences.